Successful Treatment of Leukemic Mature B-Cell Lymphoid Neoplasm with Similar Features to Splenic Marginal Zone Lymphoma Possessing Aberrant Myeloid Markers - Shinsaku Imashuku; Naoko Kudo; Kagekatsu Kubo; Katsuyasu Saigo (Case Reports in Hematology)
In splenic marginal zone lymphoma (SMZL), there are cases that cannot accurately be classified as such because of overlapping morphologic and/or immunophenotypic features. We report here a 76-year-old Japanese female, who showed leukemic B-cell lymphoproliferative disease possessing characteristic features identified for SMZL. The patient was leukemic with white blood cell counts 49,400/µL (abnormal cells, 78.5%) and neoplastic cells were characterized by aberrant expression of myeloid markers with CD19+CD13+ (64.2%) and CD20+CD11c+ (25.1%). Considering her history of previous chemotherapy and systemic leukemic phase of the disease, we treated the patient without performing splenectomy, with successful use of a combination of rituximab/bendamustine hydrochloride and of rituximab/cladribine. The patient has been in a complete remission longer than 44 months, with no detectable M-protein.